2008
DOI: 10.1577/t07-185.1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Bioelectrical Impedance Analysis for Estimating Whole‐Fish Energy Density and Percent Lipids

Abstract: Abstract.-We evaluated bioelectrical impedance analysis (BIA) as a nonlethal means of predicting energy density and percent lipids for three fish species: yellow perch Perca flavescens, walleye Sander vitreus, and lake whitefish Coregonus clupeaformis. Although models that combined BIA measures with fish wet mass provided strong predictions of total energy, total lipids, and total dry mass for whole fish, including BIA provided only slightly better predictions than using fish mass alone. Regression models that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 34 publications
4
60
2
Order By: Relevance
“…BIA has already been used to successfully determine the body compositions of different fish species (Cox and Hartman, 2005;Duncan, 2008;Andrade et al, 2014), although certain authors have argued that improvements remain necessary before BIA approaches can become a useful tool for fish farming (Bosworth and Wolters, 2001;Pothoven et al, 2008). We note that particular care (regarding room temperature and the position of needles, for instance) is required during BIA readings to minimize errors.…”
Section: Discussionmentioning
confidence: 99%
“…BIA has already been used to successfully determine the body compositions of different fish species (Cox and Hartman, 2005;Duncan, 2008;Andrade et al, 2014), although certain authors have argued that improvements remain necessary before BIA approaches can become a useful tool for fish farming (Bosworth and Wolters, 2001;Pothoven et al, 2008). We note that particular care (regarding room temperature and the position of needles, for instance) is required during BIA readings to minimize errors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the quantity of water within fish flesh mainly influences the degree of resistance (Schoeller, 2000). Because body water is inversely related to body fat content as mentioned before (Craig, 1977;Schreckenbach et al, 2001) and hence water relates inversely to energy density (Chellappa et al, 1995), BIA measures have been found to correlate well with a range of body composition metrics in fish (e.g., Bosworth and Wolters, 2001;Pothoven et al, 2008;Hanson et al, 2010;Rasmussen et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…All BIA measurements were triplicated, and the distance between the two sets of needles was measured. Raw BIA measurements (resistance and reactance) and parallel-transformed raw BIA measurements (Pothoven et al, 2008) are cross-sectional measurements and should relate to relative tissue properties like relative dry mass (Rasmussen et al, 2012), whereas volumetric measurements (e.g. needle distance 2 /parallel-transformed reactance, Cox and Hartman, 2005;Hanson et al, 2010) are three dimensional measurements and should reflect whole organism properties like total body water (Rasmussen et al, 2012).…”
Section: Sampling Procedures Biamentioning
confidence: 99%
See 1 more Smart Citation
“…That study also revealed differences among the fish: it underestimated the energy density and the percentage of lipids in lipid-rich fish, and overestimated the energy density and the percentage of lipids in low-lipid fish. The different models included the following as independent variables: weight, total length, the resistance and reactance in parallel, and the relationship between the square of the length and the resistance in parallel (Pothoven et al 2008).…”
Section: Discussionmentioning
confidence: 99%